A 'Charaj model' of 'Silk and Handloom Competitiveness Index' to measure sustainable competitiveness of silk and handloom textile segment of India. (2017) - Londhe, Charulata; Gupte, Rajani
The silk and hand loom textile segment is studied from the limited aspect of competitiveness. Study of competitiveness largely deals with either the firm competitiveness, industry competitiveness or national competitiveness. Competitiveness in textile industry is also observed to be mostly focused on power loom textiles and ready-made garments only. This segment of Indian textile industry apart from generation of huge employment for skilled and semi-skilled people is a medium of traditional knowledge, skills, artistic and aesthetic value in almost all states of India. With the need of further and holistic study of competitiveness of silk and hand loom textiles segment, this paper takes efforts to develop a model to measure the sustainable competitiveness of the segment in India by identifying the 'determinants' and 'parameters' affecting the competitiveness of the segment and contributes in the research by its exploratory work.